Priests and politics at ground level. The trajectory of the parish priest of Monteros (Tucumán) during the first peronism. Curas y política a ras del suelo. La trayectoria del párroco de Monteros (Tucumán) durante el primer peronismo - Santos Lepera, Lucía (2021)
In 1952, the priest of the town of Monteros, Simón Pedro Lobo, was involved in a conflict with the director of the Normal School. As a consequence, he lost his ministerial licenses and was expelled from the diocese in 1953. The bishop based the sanction on the "political behavior" of the priest manifested in his fervent adhesion to the government of Perón. The article aims to analyze the conflict that involved the priest, the director and the church hierarchy, taking into account the links built by Lobo since his arrival at the parish. Through the analysis of his trajectory in Monteros, it is possible to study the social and political modes of intervention, as well as the social networks in which the priest participated before and after the irruption of Peronism. The paper adopts a “ground level” approach and restores the community links in order to explain the positions of the parish priest and the tensions originated with the ecclesiastical hierarchy.